Profil Indeks Massa Tubuh dan Daya Tahan Kardiovaskular (Vo₂Max) Peserta Ekstrakurikuler Bola Voli Sekolah Menengah Atas - Angga Dwi Saputra; Hariyoko Hariyoko (Pusat Riset dan Inovasi Nasional, 2025)
Volleyball athletes need an ideal BMI because they must be able to master the basic techniques of the game of volleyball. In addition, some positions also require ideal BMI such as spikers and blockers to support the success of basic techniques. Volleyball is a sport that requires continuous movement over a long period of time, so in this case the maximum oxygen volume (VO₂Max) is very necessary. Based on the description presented, it is very important to know cardiovascular endurance and body mass index profile to be evaluation material and to support achievements. This study aims to examine the body mass index and cardiovascular endurance profile of volleyball extracurricular participants of SMA Negeri 1 Sungai Loban. The method used in this study is a quantitative descriptive type survey. The population in this study is 21 participants taken as a sample. Based on the measurement results, the body mass index of volleyball extracurricular participants was obtained from 14 participants (66.67%) in the ideal weight category. Meanwhile, the cardiovascular endurance of 11 male participants (69%) was included in the very poor category, 5 male participants (31%) in the poor category, and 2 female participants (40%) in the very poor category, 3 female participants (60%) in the poor category. From the data that has been obtained, it can be concluded that the body mass index is classified as the ideal weight category while cardiovascular endurance is classified as very lacking.